Study on Antioxidant Activity of Fermented Rice Bran and Skim Milk by Probiotic Lactic Acid Bacteria (Lactobacillus plantarum J2 and Lactobacillus casei) - Zubaidah, Elok; Aldina, Nawa; Nisa, Fithri Choirun (Jurnal Teknologi Pertanian, 2010)
Rice bran is a by product from rice milling that contains more than 20% of dietary fiber, mostly composed of insoluble fibers. Rice bran also contains antioxidants in high level such as tocopherol, tocotrienol, oryzanol and phenolic. More than 1% of these phenolic antioxidants are covalent bounded with insoluble fibers in rice bran that lowers the bioavailability of phenolic. To increase the bioavailability of phenolic antioxidants, microorganisms such as LAB (probiotic) that can produce enzyme to degrade fibers are used.  In this research skimmed milk is also used to compare the antioxidant activity in milk based and rice bran based probiotic products.Randomized Block Design was used with 2 factors, type of substrats in 2 level (rice bran and skimmed milk) and type of isolates in 2 level (L. plantarum J2 and L. casei).  The resulted data then were analyzed using ANOVA (?=5%) and differential test BNT (?=5%).  The results of this experiment showed that indigenous probiotic isolate L. plantarum J2 was more effective to increase the antioxidant activity compared to L. casei in fermented rice bran.  It was because L. plantarum J2 could degrade fibers and increase bioavailability of phenolic antioksidant within 12 hours fermentation.  The best treatment was fermented rice bran media with indigenous isolate L. plantarum J2.  The best treatment had caharacteristics as followed: LAB total amount of 3.68.1011 cfu/ml, total acid of 1.053%, pH of 3.93, insoluble fiber content of 1.20%, total of phenolic cintent of 52.07 ppm, and antioxidant activity of 88.86%.Keywords: indigenous LAB isolate, rice bran, total phenolic, antioxidant actvity